VARIOUS TRAITS OF PB-2 BIRD IN INTENSIVE SYSTEM OF MANAGEMENT - M. AHMED, N. KALITA1 ; N. PATHAK (Indian Journal of Animal Production and Management, 2017)
An experiment was conducted to study the different traits of PB-2 bird being maintained under AICRP on Poultry Breeding, Department of Poultry Science, College of Veterinary Science, Assam Agricultural University, Khanapara, Guwahati-22 under intensive system of rearing. The result in respect of body weight, conformation traits, feed conversion ratio, mortality and carcass traits were recorded during the study. Key words: PB-2 bird, Age at sexual maturity, Hatchability, Carcass traits.